The Relationship Between Food Availability And Diversity to The Nutritional Status Of Adolescents In Bekasi - Khoirul Anwar; Fitri Kusumaningtyas (Jurnal Andaliman: Jurnal Gizi Pangan, Klinik dan Masyarakat, 2023)
Adolescence is a phase that has the second highest growth rate after early childhood. Adequate adolescent nutritional intake will support good nutritional status. Nutritional status in adolescents is influenced by several factors including socio-economic, food diversity, and food availability. The purpose of this study was to determine the relationship between food availability and food diversity on the nutritional status of adolescents at SMKN 2 Bekasi City. The research design used a cross-sectional study. Respondents were selected by Cluster Random Sampling with a total of 101 respondents. The test used in this study is the Chi-Square test. The results of this study showed that 13.9% of respondents experienced malnutrition, 66.3% of respondents' families were classified as food insecure and 33.7% of respondents had low food diversity. There is a relationship between the nutritional status of adolescents with food availability and food diversity (p <0.05). The conclusion is that there is a relationship between food availability and food diversity on the nutritional status of the respondents.Keywords— Food Diversity, Availability, Adolescents, Nutritional Status